Meta-Analysis of the Influence of Social Media on Students' Cooking Skills in the Implementation of Pastry Bakery Subjects - silaban, Silpia; Nainggolan, Sindi Judiati; Ingtyas, Fatma Tresno; Sabrina, Elsa (CV. Tripe Konsultan, 2024)
This study aims to explore the impact of social media on students' cooking skills in the implementation of Pastry Bakery subjects using a meta-analysis method. Social media platforms, such as Instagram, TikTok, and YouTube, have become significant tools in education, offering easy access to interactive and visual learning content. The study analyzes 15 relevant articles, with results indicating that social media has a moderate positive influence (effect size = 0.50) on improving students' cooking skills. Platforms like YouTube enable students to follow step-by-step tutorials, while Instagram and TikTok facilitate peer interaction through challenges and online communities.The analysis reveals that social media can enhance the understanding of cooking techniques, develop practical skills, and boost learning motivation through visualization and interactivity features. However, challenges such as distractions and content quality must be addressed. Teachers play a crucial role in effectively utilizing social media, for instance, by providing reliable resources and creating appropriate educational content.These findings indicate that social media, when used wisely, can be an effective complement to traditional teaching methods. This research is expected to provide insights for educators on integrating technology into vocational education curricula, particularly in the pastry and bakery field, to optimally support students' skill development.